Effects of general and spinal anesthesia on postoperative rehabilitation in older adults after lower limb surgery: a retrospective cohort study - Li, Guifei; Ma, Qingjing; Li, Yizhen; Tan, Furong; Li, Xuan; Chen, Jie (Frontiers in Medicine, 2024)
Objective To investigate the effects of perioperative general anesthesia (GA) and spinal anesthesia (SA) on postoperative rehabilitation in elderly patients with lower limb surgery. Methods This retrospective propensity score-matched cohort study included patients aged 65 years or older who underwent lower limb surgery between January 1, 2020, and May 31, 2023. The GA and SA were selected at the request of the orthopedic surgeon, patient, and their family members. The main outcomes included the incidence of the patient’s inability to self-care at discharge, postoperative complications including pulmonary infection, thrombus of lower extremity veins, infection of incisional wound and delirium, length of hospital stay, and incidence of severe pain in the first 2 days postoperatively. Results In total, 697 patients met the inclusion criteria, and 456 were included in the final analysis after propensity score matching. In the GA and SA groups, 27 (11.84%) and 26 (11.40%) patients, respectively, could not care for themselves at discharge. The incidence rates did not differ between the groups (p = 0.884). In contrast, the incidence of postoperative complications (GA: 10.53% and SA: 4.39%; p = 0.013) and the length of hospital stay (GA: 16.92 ± 10.65 days and SA: 12.75 ± 9.15 days; p < 0.001) significantly differed between the groups. Conclusion The choice of anesthesia is independent of the loss of postoperative self-care ability in older patients (>65 years) and is not a key factor affecting postoperative rehabilitation after lower limb surgery. However, compared with GA, SA reduces the incidence of postoperative complications and a prolonged hospital stay. Thus, SA as the primary anesthetic method is a protective factor against a prolonged hospital stay.